New challenges for the teaching of architecture - Alba-Dorado, María Isabel (My University, 2019)
The implementation of the European Higher Education Area (EHEA) opens us to a new scenario marked by a training model increasingly complex and extensive in time that differs considerably from that which has been done so far and that makes it necessary to think again University. In this context, it is necessary to review the teaching model of the current Schools of Architecture: defining new strategies and reflection mechanisms according to the expectations of the degree and the postgraduate in our country and reconsidering the ways of teaching and learning, taking into account not only the what you want to teach, but also to how you are going to teach in order to move from the traditional model of transmission of knowledge from teacher to student, to a model based on the development of competences in the student, in which knowledge stops be stable and scarce to demand its expansion and update constantly throughout life and where the educational institution loses its exclusivity when transmitting knowledge and information. All this makes it necessary for the student to reach the capacity to acquire all those knowledge, skills and attitudes that will require throughout his life in his academic or professional training becoming the true protagonist of his own training. For this, it is necessary to think of a teaching of architecture that defines more flexible learning pathways that support ongoing training. A teaching oriented more to show an attitude towards the project, to encourage, stimulate and involve students in their own learning process helping them to develop their capacity to learn to learn. In short, a teaching is demanded in which the training on information predominates with the aim of creating learning situations that facilitate a subsequent continuous training and that allow a more critical and deep intellectual development that enables to generate knowledge.
Keywords: Arquitectura; Architecture; Architectural project; Teaching; Learning